Increased fracture risk in plasma cell dyscrasias is associated with poorer overall survival. (27th June 2017) - McIlroy, Graham; Mytton, Jemma; Evison, Felicity; Yadav, Punit; Drayson, Mark T.; Cook, Mark; Pratt, Guy; Cockwell, Paul; Pinney, Jennifer H.
Summary: Pathological fractures are a common complication of plasma cell dyscrasias (PCD) and are associated with significant morbidity. Routine use of bisphosphonates over the past decade has aimed to reduce the risk of fractures in patients with multiple myeloma, but despite this, fractures continue to represent a significant burden of disease. In this study we report the fracture rate of hospital in‐patients with PCD in England. Data from the national registry Hospital Episode Statistics between 2001 and 2015 were used to determine fracture rate and its effect on overall survival. Fracture rates were 17·8 times higher than the general population in the first year after admission with PCD, and remained elevated for up to 10 years after first admission. The increased fracture risk preceded the first admission with PCD and, conversely, the incidence of PCD increased after admission with one or more fractures. Overall survival is improving with PCD, however poorer survival is found in patients with a preceding fracture (Hazard ratio 1·20). Despite widespread bisphosphonate use, fractures remain common in PCD, and are associated with poorer outcomes.